248 Relationships Between Sow and Litter Parameters and Sow Rectal Temperature at the End of Farrowing. (12th April 2022) - Vande Pol, Katherine D; Shull, Caleb M; Ellis, Michael
Abstract: There is evidence that sow rectal temperature during farrowing may be associated with farrowing duration and difficulty, and stillbirth rates. However, factors affecting sow temperature during parturition have not been well quantified. The objective of this study was to evaluate relationships between sow and litter parameters and sow rectal temperature at the end of farrowing. Data (1005 sows/litters) were from 5 studies conducted on the same commercial farrowing facility with the same management. Independent variables included sow parity, use of farrowing induction, number of piglets born alive, litter weight, farrowing duration (on a sub-sample of 289 litters), and room temperature at the start of farrowing. Sow temperature at the end of farrowing averaged 38.5 ± 0.53°C. Data were analyzed using PROC REG of SAS. Models accounted for the linear, quadratic, and cubic effects of continuous independent variables, and/or the categorical effect of farrowing induction. Sow rectal temperature at the start of farrowing had a positive relationship with sow temperature at the end of farrowing and the greatest R 2 value (0.33; Table 1). Individually, sow parity, farrowing duration, and induction were related ( P ≤ 0.05) to sow rectal temperature at the end of farrowing. However, these factors explained a small proportion of the variation (R 2 ≤ 0.05) in sow temperature. For the multivariate model, only room temperature and sow rectal temperature at the start of farrowing were related ( P ≤ 0.05) to temperature at the end of farrowing, explaining 34% of the variation. In conclusion, these results suggest that sow temperature at the start of farrowing had the greatest influence on temperature at the end and that other factors (sow parity, farrowing duration, farrowing induction, and room temperature) were relatively unimportant.